Theoretical foundations of movement control in the process of training athletes in combat sports - Novakovsky, S. V.; Maksimovich, V. A.; Rudenik, V. V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to develop theoretical and methodological foundations for the formation and improvement of movement control mechanisms in the process of training athletes in combat sports.